Visitors’ risk awareness on water-based recreational activities at Teluk Batik Beach, Lumut, Perak - Rosli, Arifah (2018)
Water-based recreation activities are increasingly getting a place in the heart of recreation activities fans. Like other recreational activities, water-based activities also have their own risks that most people are not aware. Hence, the safety of those involved in these activities should be well taken care by relevant authorities. This study was conducted to determine the level of visitors‟ awareness on the risk of water-based recreational activities at the Teluk Batik Beach, Lumut, Perak. Data were collected using questionnaire involving 200 respondents who participated in water-based recreation activities in the study area. Majority of respondents are aware of the level of risk they face when doing water-based recreational activities at Teluk Batik Beach. Undeniably, the results of this study may have implications on the existing water-based recreation operators or business, in general.